An Analysis of Hate Speech in Lucas's Instagram Post: Pragmatics Study - Amalia, Khoerunnisa; Nugraha, Deden Novan (Universitas Galuh, 2024)
Hate speech is a behavior, word, writing, or act that is prohibited because it can trigger acts of prejudice and violence on a victim, perpetrator of violence, or the statement. This research aims to investigate the types of hate speech and find out the meaning of these types of hate speech. This research takes data from Instagram and comments on @lucas_xx444. As a former member of NCT and WayV, the data was analyzed using qualitative methods. A multifaceted approach to comprehensively understanding and addressing hate speech, recognizing its social deviance, and advocating for collective efforts to create environments that prioritize respect, equality, and unity. The results of the research found six types of hate speech in the comments column: provoking, inciting, insulting, blasphemy, defamation, and spreading hoaxes.